Implementation of THE CEDAW in France and Indonesia: Challenges and Progress Towards a Unified Approach to Women's rights - Maret, Louna (Indonesian Journal of International Law, 2024)
Almost fifty years after the adoption of the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) and 189 ratifications, it is interesting to analyze the progress and challenges remaining regarding a unified approach to women’s rights. This paper will focus on Indonesia and France, two countries with different cultural backgrounds and approaches regarding human rights. The research methods are mostly based on lectures of legal journal articles, papers, and recent periodic reports of the Committee that ensure the implementation of the CEDAW. After recalling the historical context of women’s rights in both countries to highlight the challenges that are already present before CEDAW and analyzing the last period’s reports considering articles of the CEDAW to identify progress and challenges remaining, we can conclude that women’s rights through the implementation of CEDAW are still falling short on men’s rights. A worldwide problem seems to be persistent: patriarchal values. A unified approach of the CEDAW is essential to ensure women’s rights worldwide, considering that women’s rights are universal and not just based on Western standards.